Evaluation of urinary γ‐glutamyl transferase and serum creatinine in non‐azotaemic hospitalised dogs. (13th July 2019) - Perondi, Francesca; Lippi, Ilaria; Ceccherini, Gianila; Marchetti, Veronica; Guidi, Grazia
Abstract : Urinary and blood biomarkers for diagnosis of acute kidney injury (AKI) in hospitalised dogs were evalueted. This prospective study included 97 dogs, classified according to the International Renal Interest Society classification into no AKI and AKI grade 1 (48‐hour increase in serum creatinine≥0.3 mg/dl and/or urinary production <1 ml/kg/hour for at least six hours). A total of 62 of 97 dogs (64 per cent) were classified as AKI 1. A statistically significant difference was found between no AKI and AKI 1 in urine protein to creatinine ratio, urinary γ‐glutamyl transferase (uGGT) and uGGT/cu (P<0.0001). Thirteen of 97 dogs (13.4 per cent) that developed increased creatinine and change in AKI grade showed high mortality (n=9/13; 69.2 per cent). The receiver operating characteristic (ROC) curve analysis of uGGT/cu index as a marker for AKI grade 1 had an area under the ROC curve of 0.78; optimal cut‐off point was 57.50 u/g, with sensitivity and specificity of 75.4 per cent and 75.6 per cent, respectively. Overall intensive care unit mortality was 23.7 per cent (23/97), 13.4 per cent (13/97) of which died during hospitalisation and 10.3 per cent (10/97) within 28 days after discharge. uGGT is an acceptable marker for distinguishing between AKI 1 and no AKI.